Validation of UV-Visible and HPLC method for the determination of sodium p-aminosalicylate and m-aminophenol in a new pharmaceutical formulation - Hergert, Lisandro Yamil (2015)
Sodium p-aminosalycilate is an orphan drug used in patients affected with multidrug-resistant Tuberculosis. Two methods, high-performance liquid chromatographic and ultraviolet spectrophotometric for the quantitative determination of sodium p-aminosalycilate and its degradation productm-aminophenol in a new pharmaceutical formulation, powder for extemporaneous reconstitution, were developed in the present work. The parameters linearity, precision, accuracy, specificity, robustness, limit of detection, and limit of quantification were also studied. Chromatography was carried out by reverse-phase technique on an RP-18 column with a mobile phase composed of 50 mM monobasic/dibasic phosphate buffer and methanol (42.5:42.5:15 v/v/v) with 1.9 g of hidroxytetrabutyl ammonium ionic pare adjusted to pH 7.0 with orthophosphoric acid. The ultraviolet spectrophotometric method was performed at 254 nm and 280 nm for quantification of sodium p-aminosalycilate and m-aminophenol, respectively. The proposed methods are highly sensitive, precise, and accurate and can be used for the reliable quantification of sodium p-aminosalycilate in the new alternative formulation. High-performance liquid chromatographic approach demonstrated to be a stability-indicating method, therefore suitable for the investigation of the chemical stability of sodium p-aminosalycilate.